2021
DOI: 10.20944/preprints202111.0316.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Current Trends in Urban Conservation: Medieval Historic Arab City Centers

Abstract: As Arab countries are beginning to recover from the socioeconomic impacts of the COVID-19 pandemic, conservation programs are restarting. Noticeably, traditional conservation efforts have not helped improve the poor living conditions in most historic urban centers of Arab cities due to many reasons such as a lack of funds, urban management policies, and the narrow scope of conservation projects. In 2016, the UN urban agenda recognized tangible and intangible heritage as the basis for sustainable, vibrant, urba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It can be observed that many historical Arab cities follow similar organisational concepts and construction methods. Their urban tissue has developed as a result of social and historical processes and is demonstrated via specific, characteristic features of the urban plan and spatial layout (Jasim, 2016, Shehata, 2022. Residential quarters were usually shaped with narrow curved streets and located not far from the minarets.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…It can be observed that many historical Arab cities follow similar organisational concepts and construction methods. Their urban tissue has developed as a result of social and historical processes and is demonstrated via specific, characteristic features of the urban plan and spatial layout (Jasim, 2016, Shehata, 2022. Residential quarters were usually shaped with narrow curved streets and located not far from the minarets.…”
Section: Theoretical Backgroundmentioning
confidence: 99%